FINANCIAL TECHNOLOGY (FINTECH) DALAM PERSPEKTIF AKSIOLOGI - Suryono, Ryan Randy (Kementerian Komunikasi dan Informatika R.I., 2019)
A technology is generated from the development of science which is then implemented in society. Changes in science to technology are inseparable from scientists. A scientist will be confronted with personal interests or interests of the general public which bring to the issue of scientific ethics and value-free problems. Likewise with the progress of e-finance and mobile technology for financial companies. This prompted Fintech's innovation to emerge after the global financial crisis in 2008 by combining e-finance, internet technology, social networking services, social media, artificial intelligence, and Big Data analytics. In addition, with the development of the digital economy, Fintech is present as an innovation. But in its development, there are still positive and negative issues from the application of Fintech that provide many new perspectives that lead to moral and ethical issues. By adopting the Kitchenham Systematic Literature Review (SLR) approach, this study identifies what problems occur in the development of Fintech. Using three databases, including SCOPUS, ScienceDirect, and IEEE Xplore and Mendeley devices for journal database management, this study attempts to formulate an understanding of Fintech, Fintech variety, trends and Fintech innovations, what problems arise from Fintech innovation and how solutions are implemented Fintech